The Influence of Liquidity Toward Capital Structure - Paramita, Astriyani Sandya; Suhardjo, Yohanes; Asri, Marwan (E-Jurnal Akuntansi; Vol 31 No 11 (2021)DO - 10.24843/EJA.2021.v31.i11.p10, 2021)
Globalization and technological developments in the business world, both in the industry are growing rapidly. Most of the manufacturing companies use the debt as their capital structure which can be seen from the fluctuation of debt to equity (DER) ratio in 2014-2017. This research aims to examine the influence of liquidity toward capital structure in manufacturing companies listed on the Indonesia Stock Exchange for the 2014-2018 period, which are grouped by the company size.  The multiple linear regression analysis is used to test the hypothesis.  The results of this research indicate that liquidity has a negative influence toward leverage, reflects that the higher the liquidity of a company, the lower the level of leverage and vice versa. There is a consistency between large and small companies regarding the effect of liquidity on leverage. Capital structure for large and small companies still choose internal funds as the first choice. Keywords : Capital Structure; Liquidity; Large Companies; Small Companies.